Identifikasi Peptida BioaktIf dari Olahan Susu Fermentasi Tradisional Indonesia Sebagai Bahan Pangan FungsIonal Untuk Kesehatan - Soenarno, M. S.; Polli, B. N.; Febriantosa, A.; Hanifah, R. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2013)
Dangke and dadih is milk processing product from South Sulawesi and West Sumatera. Dangke had total plate count, yeast and mold, and lactic acid bacteria, respectively 6,4 x 108 cfu/g, 2,5 x 108 cfu/g, 2,8 x 105 cfu/g; and dadih had 7,3 x 108 cfu/mL, 9,0 x 107 cfu/mL, 1,5 x 105 cfu/mL. Dangke and dadih had higher sensitivity to Gram positive than Gram negative bacteria. Based on protein molecular weight, then dangke and dadih had peptide that included to glicoprotein.